The Bioarchaeology of Socio-Sexual Lives : Queering Common Sense About Sex, Gender, and Sexuality - Geller, Pamela L. (Springer International Publishing : Imprint: Springer, 2017)
This volume uses bioarchaeological remains to examine the complexities and diversity of past socio-sexual lives. This book does not begin with the presumption that certain aspects of sex, gender, and sexuality are universal and longstanding. Rather, the case studies within-extend from Neolithic Europe to pre-Columbian Mesoamerica to the nineteenth-century United States- highlight the importance of culturally and historically contextualizing socio-sexual beliefs and practices. The Bioarachaeology of Socio-Sexual Lives highlights a major shortcoming in many scholarly and popular presentations of past socio-sexual lives. They reveal little about the ancient or historic group under study and much about Western society's modern state of heteronormative affairs. To interrogate commonsensical thinking about socio-sexual identities and interactions, this volume draws from critical feminist and queer studies. Reciprocally, bioarchaeological studies extend social theorizing about sex, gender, and sexuality that emphasizes the modern, conceptual, and discursive. Ultimately,The Bioarchaeology of Socio-Sexual Lives invites readers to think more deeply about humanity's diversity, the naturalization of culture, and the past's presentation in mass-media communications.
Keywords: Social sciences.; Anthropology.; Archaeology.; Sociology.; Sex (Psychology).; Gender expression.; Gender identity.; elektronické knihy; electronic books